Synthesis of the SrFeO2.5 and BaFeO3-x perovskites by thermal decomposition of SrNh4[Fe(Cn)6] 3H2O and BaNh4[Fe(Cn)6] - Córdoba, Lucrecia M. (2008)
In the present work the synthesis, physicochemical characterization and thermoanalytical results of SrNh4[Fe(Cn)6] 3H2Oy BaNh4[Fe(Cn)6] are described. The thermal decompositions in oxygen atmosphere for both salts are carried out in the stages that lead to the formation of mixed oxides, i. e., SrFeO2.5 and BaFeO3-x at 1173 K. Barium carbonate is also obtained in the residue in the case of the decomposition of the barium complex. The total weight loss are 49,95% and 35,45 % for the strontium and barium salts, respectively. A decomposition mechanism is suggested for the pyrolisis processes from the data provided by IR spectroscopy, X-ray powder diffraction and chemical analysis. The specific surface area of the obtained oxides is also determined in order to evaluate its eventual catalytic activity.